Motivational Teaching Practices of Teachers in Higher Education: A Convergent Parallel Design - Ray Jean Anne S. Alivio; Peter John E. Amaya; Rachel Ann O. Lopez; Cristy Grace A. Ngo (Scientia Publica Media, 2026)
This study investigated the motivational teaching practices employed by teachers in higher education institutions (HEIs) in Davao City, Philippines. Despite advancements in curricula, student motivation remains a significant challenge, often resulting in low engagement and academic performance. The research aimed to assess the extent to which teachers apply motivational strategies across four dimensions: creating basic motivational conditions, generating initial motivation, maintaining motivation, and encouraging positive self-evaluation. A convergent parallel mixed-methods design was utilized. Quantitative data were gathered from a survey of 120 purposively selected teachers using an adapted instrument (5-point Likert scale), while qualitative insights were obtained through semi-structured interviews with 10 teachers. Quantitative results showed that teachers frequently create basic motivational conditions (M=3.91) and maintain motivation (M=3.86), though generating initial motivation was practiced to a moderate degree (M=3.39). Qualitative analysis revealed five themes: encouraging respectful environments, inspiring through enthusiasm, engaging through storytelling, motivating through approachability, and sustaining engagement via interactive activities. Triangulation confirmed that student motivation flourishes when teachers form meaningful relationships, demonstrate authentic enthusiasm, and link lessons to students’ everyday lives. The study concluded that effective motivation in higher education is relational and human-centered. It underscores the importance of teacher empathy and authenticity in promoting lasting student engagement.